USING STORIES IN TEACHING ENGLISH TO YOUNG LEARNERS - Kasimov , Anvar; Eshmo‘minov , Elbek (Educational Research in Universal Sciences, 2023)
The main aim of writing this article to identify how is useful stories to teach young learners because they are interested in fiction and non fiction events that’s why teachers definitely can use different little stories to improve reading and speaking skills.